John Hunt Morgan and His Raiders - Thomas, Edison H. (Book collections on Project MUSE., 1985)
Whether one things of him as dashing cavalier or shameless horse thief, it is impossible not to regard John Hunt Morgan as a fascinating figure of the Civil War. He collected his Raiders at first from the prominent families of Kentucky, though later the exploits of the group were to attract a less elite class of recruits. Morgan was able to lead these men into the most dangerous adventures by convincing them that the honor of the South was at stake; yet he did not always succeed in appealing to that sense of honor when temptations of easy theft drew the Raiders from military objectives to w.